Muskox ( Ovibos moschatus ) milk. I. Gross composition, fatty acid, and mineral constitution - Baker, B. E.; Cook, H. W.; Teal, J. J. (Canadian Journal of Zoology, 1970)
Milk was obtained from five muskoxen of an experimental herd maintained at the University of Alaska. The gross composition and mineral and fatty acid constitution of the milk were determined.